2008
DOI: 10.1001/archpsyc.65.2.135
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of μ-Opioid Receptor (OPRM1) as a Predictor of Naltrexone Response in the Treatment of Alcohol Dependence

Abstract: clinicaltrials.gov Identifier: NCT00006206.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
136
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(141 citation statements)
references
References 52 publications
5
136
0
Order By: Relevance
“…While the amount of therapy provided was not extensive and is not as specific as cognitive behavioural therapy (CBT), it is possible that the nine sessions of BRENDA therapy could have interfered with finding a significant pharmacogenetic effect via a ‘ceiling effect’. A similar explanation was proposed by Anton et al, [58] who found no effect when subjects who received the CBI were included in the analysis.…”
Section: Clinical Pharmacogenetic Treatment Trialssupporting
confidence: 69%
See 1 more Smart Citation
“…While the amount of therapy provided was not extensive and is not as specific as cognitive behavioural therapy (CBT), it is possible that the nine sessions of BRENDA therapy could have interfered with finding a significant pharmacogenetic effect via a ‘ceiling effect’. A similar explanation was proposed by Anton et al, [58] who found no effect when subjects who received the CBI were included in the analysis.…”
Section: Clinical Pharmacogenetic Treatment Trialssupporting
confidence: 69%
“…A higher percentage of subjects with abstinence or a controlled, non-risky drinking pattern, and low ratings of alcohol-related consequences also had the Gallele (p= 0.005, OR= 5.75, 95% CI 1.88, 17.54). [58,59] …”
Section: Clinical Pharmacogenetic Treatment Trialsmentioning
confidence: 99%
“…For example, a secondary analysis of the COMBINE study (Anton et al 2006) was designed to examine whether patients heterozygous (Asp40/Asn40) or homozygous (Asp40/Asp40) for the mu-opioid receptor gene (ORPM1) Asp40 allele responded better to naltrexone (Anton et al 2008). Results of the genotyping in 911 of the 1383 patients demonstrated that patients receiving naltrexone as well as medication management to have a significantly greater response if that individual had at least one copy of the OPRM1 Asp40 allele (Anton et al 2008).…”
Section: The Potential Contribution Of Subtype Classifications In Thementioning
confidence: 99%
“…Results of the genotyping in 911 of the 1383 patients demonstrated that patients receiving naltrexone as well as medication management to have a significantly greater response if that individual had at least one copy of the OPRM1 Asp40 allele (Anton et al 2008).…”
Section: The Potential Contribution Of Subtype Classifications In Thementioning
confidence: 99%
“…While the value of the single-nucleotide polymorphism (SNP) of the μ-opioid receptor (OPRM1 Asn40Asp) to guide pharmacotherapy in opioid dependence remains uncertain, the search for other SNPs and more complex models integrating multiple genes with environment continues. [36][37][38][39] Another category of predictors of addiction severity and treatment response not usually employed in clinical trials and practice includes symptom provocation, such as drug craving in response to drug-related cues. [40][41][42][43] To some extent, this is analogous to a cardiac stress test or a glucose tolerance test in medicine.…”
mentioning
confidence: 99%